The extended Inclusion of Nature in Self scale. (September 2016) - Martin, Christian; Czellar, Sandor
Abstract: By relying on various theoretical paradigms, extant research has developed several measurement tools for the assessment of individual environmental identity. One of the most important such tools is the Inclusion of Nature in Self measure (INS; Schultz, 2001). In comparison to other measures, the INS is very concise and easy to administer. However, because of its single-item nature, its psychometric properties and applicability domains are limited in scope. The present research proposes a four-item development of the INS – the Extended Inclusion of Nature in Self (EINS) scale. In Study 1, we explore the relevance of spatial metaphors in the assessment of self-nature connection. Based on the insights from this study, we develop an extended version of the INS and investigate its dimensionality, reliability, and validity across 5 studies. Our studies converge in suggesting that the proposed EINS is psychometrically stronger than the original INS, compares well in criterion-related validity to extant verbal scales, and has broader research applicability. Highlights: Self-nature connection is studied from a cognitive self-expansion perspective. The extant measure from this perspective – the one-item Inclusion of Nature in Self measure – has advantages and drawbacks. Based on additional metaphors, a four-item extension of the Inclusion of Nature in the Self measure is developed. The scale shows superior psychometric properties to the original INS, circumvents its drawbacks and keeps its advantages.